Zakah index: Islamic economics’ welfare measurement - Kumara Adji Kusuma; Muhamad Nafik Hadi Ryandono (Indonesian Journal of Islam and Muslim Societies, 2016)
Zakah is one of the five pillars of Islam. Compared to the other pillars, Zakah intersects with most the human dimensions: spiritual, individual, social, economic, and is quantifiable. Zakah also fulfills all of the aspect of the Maqas}id al-Shari‘ah that preserves public interests (maslahah). This paper argues that the lack of full observance of the objectives of the obligation in performing Zakah, which is intended to increase the welfare/wellbeing of the society, makes Islamic Economics as a discipline completely ineffective and inefficient in performing its essential characteristics in fulfilling the Maqas}id al-Shari‘ah. The expected outcome of this study is Zakah Index that will represents the monitoring of Zakah payment in Islamic or Muslim populated country, hence providing academics, students, society, and policy maker in Islamic or Muslim populated country an alternative measurement of economic progress, instead of Gross Domestic Product (GDP). The method used in the conceptualization of the Index and its derivatives are content analysis and conventional literature. Finally, Zakah Index is intended to be as an Islamic Economics tool to measure not only the welfare/wellbeing of Islamic Society, but also its religious (spiritual). On the last part of the paper, the Zakah Index Model then is applied to the East Java province. Zakah adalah salah satu rukun Islam. Dibandingkan dengan pilar yang lain, zakah bersinggungan dengan hampir seluruh dimensi manusia: spiritual, individual, sosial, ekonomi dan ia dapat diukur. Selain itu, zakah juga memenuhi seluruh aspek Maqas}id al-Shari‘ah yang bertujuan melindungi kepentingan umum (maslahah). Paper ini didasarkan pandangan bahwa minimnya pengawasan kewajiban pembayaran zakah, yang ditujukan untuk meningkatkan kesejahteraan masyarakat, menjadikan Ilmu Ekonomi Islam sebagai disiplin tidak efektif dan efisien dalam menjalankan karakteristik utamanya untuk memenuhi tujuan Shariah. Luaran dari studi ini adalah Indeks Zakah yang akan merepresentasi pengawasan pembayaran Zakah di Negara Islam atau masyarakat mayoritas muslim, yang dengan demikian menyediakan alternatif pengukuran kemajuan ekonomi bagi pemerintah, akademisi, dan masyarakat daripada menggunakan Produk Domestik Bruto (PDB). Metode penyusunan konsep indeks ini dengan berbagai derivasinya adalah content analysis dan metode induktif yang meliputi literatur Islam dan konvensional. Akhirnya, Indeks Zakah ini dimaksudkan menjadi “tool” Ilmu Ekonomi Islam untuk mengukur tidak hanya kesejahteraan masyarakat muslim, namun juga aspek religiusitasnya. Pada bagian akhir paper ini, model Indeks Zakah ini dipalikasikan di Provinsi Jawa Timur.